Cleavage of β-Catenin and Plakoglobin and Shedding of VE-Cadherin during Endothelial Apoptosis: Evidence for a Role for Caspases and Metalloproteinases - Herren, Barbara (The American Society for Cell Biology, 1998)
Growth factor deprivation of endothelial cells induces apoptosis, which is characterized by membrane blebbing, cell rounding, and subsequent loss of cell–matrix and cell–cell contacts. In this study, we show that initiation of endothelial apoptosis correlates with cleavage and disassembly of intracellular and extracellular components of adherens junctions. β-Catenin and plakoglobin, which form intracellular links between vascular endothelial cadherin (VE-cadherin) and actin-binding α-catenin in adherens junctions, are cleaved in apoptotic cells. In vitro incubations of cell lysates and immunoprecipitates with recombinant caspases indicate that CPP32 and Mch2 are involved, possibly by initiating proteolytic processing. Cleaved β-catenin from lysates of apoptotic cells does not bind to endogenous α-catenin, whereas plakoglobin retains its binding capacity. The extracellular portion of the adherens junctions is also altered during apoptosis because VE-cadherin, which mediates endothelial cell–cell interactions, dramatically decreases on the surface of cells. An extracellular fragment of VE-cadherin can be detected in the conditioned medium, and this “shedding” of VE-cadherin can be blocked by an inhibitor of metalloproteinases. Thus, cleavage of β-catenin and plakoglobin and shedding of VE-cadherin may act in concert to disrupt structural and signaling properties of adherens junctions and may actively interrupt extracellular signals required for endothelial cell survival.